Bisguanidines with biphenyl, binaphthyl, and bipyridyl cores: proton-sponge properties and coordination chemistry - Maronna, Astrid Christine; Hübner, Olaf; Enders, Markus; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2013)
Herein, we report on the synthesis, protonation, and coordination chemistry of chelating guanidine ligands with biphenyl, binaphthyl, and bipyridyl backbones. The ligands are shown to be proton sponges, and this protonation was studied experimentally and by using quantum-chemical calculations. Group 10 metal (Ni, Pd, and Pt) complexes with different metal/ligand ratios were synthesized. In the case of the bipyridyl systems, coordination occurs exclusively at the pyridine N atoms, as opposed to protonation. The spin-density distribution and the magnetism were evaluated for a series of paramagnetic NiII complexes with the aid of paramagnetic NMR spectroscopic studies in alliance with quantum-chemical calculations and magnetic (SQUID) measurements. Through direct delocalization from the singly occupied molecular orbitals (SOMOs), a significant amount of spin density is placed on the guanidinyl groups, and spin polarization also transports spin density onto the aromatic backbone.